Vaginal bleeding during menopause hormone therapy. Is it always endometrial cancer? How to choose the appropriate tactics for examination and management of patients? - Anna E. Protasova; Irina A. Solntseva; Ekaterina N. Vandeeva (IP Berlin A.V., 2020)
The article provides an overview of the possible causes of bleeding from the genital tract in peri- and postmenopausal women. The correct approach to patients with abnormal uterine bleeding during menopausal hormone therapy is described. A modern analysis of data on the diagnosis and treatment of postmenopausal vaginal bleeding against the background of menopausal hormone therapy was carried out. The modern possibilities of endometrial diagnostics and treatment are shown.